Otimização hit-to-lead de derivados de pirazinilpiperazinas e tiazóis contra a doença de Chagas e leishmaniose - Jacques Dit Lapierre, Thibault Joseph William (2025)
This work details the hit-to-lead optimization of two series of compounds against two parasitic neglected tropical diseases (NTDs), visceral leishmaniasis and Chagas disease. The pyrazinylpiperazine series was optimized from the LeishBox hit 1 against visceral leishmaniasis, targeting Leishmania infantum. Such optimization was achieved after an extensive structure-activity relationship study, carried out on all three structural fragments of 1. The first round of optimization, focused on the benzoyl fragment, delivered eleven compounds at least twice as potent and selective as 1. One of these was the para-hydroxyl derivative 6, which remained the most promising candidate for in vivo studies after exploring 75 compounds featuring modifications on all three structural fragments of the series. In vitro determination of its ADME profile, alongside other relevant in vivo candidates, confirmed 6 as the most relevant one for such an assessment. After reducing the parasitemia by over 90% in a BALB/c mice model of visceral leishmaniasis, this para-hydroxyl pyrazinylpiperazine derivative was effectively identified as a new lead compound for the treatment of visceral leishmaniasis, and an early investigation of its mechanism of action and molecular target was performed. The thiazole series was derived from compound 2, identified in silico and confirmed in vitro as a hit against Trypanosoma parasites. Such a status against Trypanosoma cruzi was further confirmed in the present work, and was extended from antitrypanosomal hit to anti-kinetoplastid hit after confirming its activity against Leishmania infantum. Thence, subsequent structure-activity relationship efforts identified several potent thiazole derivatives against either parasite, though the series showed radically different patterns of activity depending on the target parasite, leaving compounds active against Trypanosoma cruzi inactive against Leishmania infantum, and the other way around. After the assessment of twenty derivatives, the initial hit 2 remained the most potent thiazole against Trypanosoma cruzi, though another derivative displayed activity in the nanomolar range as well, albeit being less potent than 2. However, 2 and the most potent derivatives against Trypanosoma cruzi faced heavy limitations due to metabolic instability, preventing them from reaching in vivo assessment, despite showing a promising mechanism of action according to in vitro investigations. This metabolic liability was finally overcome by the two diamine derivatives 99 and 100, which were together with 2 the most potent thiazoles against Leishmania infantum, thus resulting in the identification of two new thiazole lead candidates against visceral leishmaniasis.